The effect of surface functionalization of nanoparticles with additives on surface tension of binary nanofluid - Muhammad, U. A.; Endrino, J. L. (Frontiers in Materials, 2025)
This study investigates how alumina nanoparticles, gum Arabic, and the surfactant 2-ethyl-1-hexanol influence the surface tension of aqueous lithium bromide (LiBr) solutions. Since surface tension, governed by intermolecular attractive forces at the liquid–solid interface, plays a key role in the performance of heat and mass transfer binary fluids, composed of water and LiBr; understanding these effects is critical for optimizing thermal systems. Lithium bromide–based heat transfer fluids were prepared from 55 wt% aqueous LiBr solutions containing alumina nanoparticles (20 nm), gum Arabic as a dispersion stabilizer, and/or 2-ethyl-1-hexanol as a surfactant. Surface tension measurements were conducted over a temperature range of 293–373 K for different fluid compositions: base LiBr solution, LiBr with nanoparticles, LiBr with gum Arabic, and LiBr with both nanoparticles and gum Arabic, with and without surfactant. The base aqueous LiBr solution exhibited surface tension values from 90.6 mN/m at 293 K to 82.7 mN/m at 373 K. The addition of alumina nanoparticles increased the surface tension by an average of 2.5%, whereas gum Arabic decreased it by approximately 2.1%. The introduction of the surfactant 2-ethyl-1-hexanol, regardless of the presence of nanoparticles or gum Arabic, led to a substantial reduction in surface tension of 32%–35%.